Prediction of Fan Tone Radiation Scattered By A Cylindrical Fuselage. Issue 1 (1st February 2022) - Rouvas, D-M.; McAlpine, A.
Abstract: A theoretical prediction method of the scattering of fan tone radiation from a turbofan inlet duct by the airframe fuselage is presented. The fan tone noise is modelled by an acoustic disc source that represents the sound field at the inlet duct termination. Adjacent to the source is a cylindrical fuselage that scatters the fan tone radiation. The prediction method is valid for upstream sound radiation. The acoustic pressure on the cylindrical fuselage is affected by refraction of the sound as it propagates through the fuselage boundary layer. This effect known as boundary layer shielding is more prominent forward of the turbofan, since the fan tone noise radiated from the inlet duct is propagating upstream. An asymptotic approach is used to model sound propagation through a boundary layer which is modelled by a thin linear shear velocity profile. Consequently the scattered pressure field can be computed very quickly, thus providing a fast and efficient prediction method. Although a realistic fuselage turbulent boundary layer does not resemble a linear shear layer, it is shown that the effect of acoustic shielding by a turbulent boundary layer can be modelled by taking a liner shear profile with a shape factor that matches the shape factor for a realistic turbulent profile.